2015
DOI: 10.1111/1755-5922.12128
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hydrogen Sulfide Prodrug, SG1002, Promotes Hydrogen Sulfide and Nitric Oxide Bioavailability in Heart Failure Patients

Abstract: SummaryRecent studies demonstrate robust molecular cross talk and signaling between hydrogen sulfide (H2S) and nitric oxide (NO). Heart failure (HF) patients are deficient in both H2S and NO, two molecules that are critical for cardiovascular homeostasis. A phase I clinical trial of a novel H2S prodrug (SG1002) was designed to assess safety and changes in H2S and NO bioavailability in healthy and HF subjects. Healthy subjects (n = 7) and heart failure patients (n = 8) received oral SG1002 treatment in escalati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
103
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 43 publications
3
103
0
3
Order By: Relevance
“…Clinical trials with SG1002 will be exciting to follow and to see if the increase in H 2 S levels translate into significant benefits in treating or preventing heart failure. Results from the initial clinical trial with SG1002 have recently been reported, demonstrating that SG1002 increases H 2 S and nitrite levels with few, mild adverse events (118). Furthermore, sulfur donors are being attached to current drug treatments, such as naproxen, improving their anti-inflammatory effectiveness and decreasing gastrointestinal and cardiovascular side effects (13,19,35,42,105).…”
Section: H 2 S Mitigates Pathological Cardiac Remodeling By Inhibitinmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical trials with SG1002 will be exciting to follow and to see if the increase in H 2 S levels translate into significant benefits in treating or preventing heart failure. Results from the initial clinical trial with SG1002 have recently been reported, demonstrating that SG1002 increases H 2 S and nitrite levels with few, mild adverse events (118). Furthermore, sulfur donors are being attached to current drug treatments, such as naproxen, improving their anti-inflammatory effectiveness and decreasing gastrointestinal and cardiovascular side effects (13,19,35,42,105).…”
Section: H 2 S Mitigates Pathological Cardiac Remodeling By Inhibitinmentioning
confidence: 99%
“…that act as H 2 S donors and have antioxidant, anti-inflammatory, and vasorelaxant properties (14,94,116,132). Slow release sulfide donors such as GYY4137 (88), SG1002 (9,78,118), AP39 (138), and S-propargyl-cysteine (58,149) (118). Because of the volatile nature and short half-life of H 2 S, a continuous, low-level H 2 S release may provide an extended therapeutic potential than a single bolus using high levels as used in many NaHS and Na 2 S studies (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been reported that the major beneficial effects of garlic rich diets are mediated by H 2 S production [57]. According to experimental, preclinical, and clinical studies [19, 303, 304], elevation of H 2 S by using dietary sources or donors could be a hopeful therapeutic strategy in addressing/managing hypertension [19]. Many antihypertensive drugs exert their protective effects at least in part by increasing NO bioavailability [15].…”
Section: Discussionmentioning
confidence: 99%
“…З десульфуразним шля-хом обміну цистеїну асоціюється продукція важ-ливої регуляторної газової молекули гідроген сульфіду (H 2 S). На сьогодні встановлено, що H 2 S відіграє важливу роль в агрегації тромбоцитів та регуляції судинного тонусу, скоротливості міокар-да, нейротрансмісії, секреції інсуліну [4,9,13,14].…”
unclassified